Satellite data receiving antenna system for pleiades neo observation satellite. Issue 1 (January 2021) - Hestrio, Y F; Soleh, M; Hidayat, A; Afida, H; Gunawan, H; Maryanto, A
Abstract: Pleiades Neo Satellite is a future optical remote sensing satellite designed for launch in 2020 with a very high spatial resolution of up to 30 cm and consists of 4 constellation satellites to continuing Pleiades-1A/1B constellation. Pleiades Neo capable of producing high temporal resolution (revisit time) in one day to collecting imagery at the same location and its performance claimed will increase up to three times when compared to the Pleiades-1A/1B constellation. LAPAN, as the main official provider in high-resolution optical satellite data in Indonesia, has planned to receive the Pleiades Neo data. This paper discusses the antenna system for receiving Pleiades Neo data by LAPAN's remote sensing ground station with analyzing the main antenna parameter requirements if Pleiades Neo will be received on Zodiac or Viasat antenna. By calculating the Carrier to Noise Ratio (C/N) value both of antenna system and compared with Airbus Defense and Space minimum C/N requirement about 13.8 dB at 5-degree elevation. The simulation result is obtained C/N value 14 dB and 6.5 dB on Zodiac and Viasat antenna, respectively. Based on the result analysis, it is found that the Zodiac antenna system is recommended for the Pleiades Neo data reception system.